Data Warehouse: A Study on Data Warehouse Technologies and its Applications in Modern Finance (International Journal of Food and Nutritional Sciences, 2022)
This study examines the use of data warehouses in the contemporary financial sector, which can assist banks with their products, departments, and institutions of profit and cost analysis. By strengthening cost management to increase efficiency, this study will significantly alter bank management departments at all levels of management, control, and means of cooperation and improve overall bank management. In addition, by establishing a data warehouse and continuously enhancing its capabilities, banks can successfully assist in the gradual standardisation of management procedures, the optimization of business processes, the improvement of asset utilisation, and the gradual realisation of the transformation of the modern commercial bank management pattern.